2016
DOI: 10.1016/j.healun.2015.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Combined pulmonary endarterectomy and balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension

Abstract: The combination of surgical PEA and interventional BPA is a new treatment option for highly selected high-risk CTEPH patients. A multidisciplinary CTEPH expert team is a basic pre-requisite for this complex concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 23 publications
0
60
0
8
Order By: Relevance
“…A preliminary study in three patients found that this strategy improved pulmonary haemodynamics and functional class [76]. However, at present this strategy remains experimental.…”
Section: Future Perspectives For Cteph Managementmentioning
confidence: 98%
“…A preliminary study in three patients found that this strategy improved pulmonary haemodynamics and functional class [76]. However, at present this strategy remains experimental.…”
Section: Future Perspectives For Cteph Managementmentioning
confidence: 98%
“…The patients underwent PTE on the operable lung and BPA on the inoperable lung during the rewarming phase of surgery. 50 Ultimately, the number of patients with clot distribution likely to benefit from this approach is small, and as already demonstrated in a previously published series, 42 BPA may emerge as a reliable tool for the treatment of residual PH after PTE. As the collective BPA experience grows, there will assuredly be an interest in comparing BPA directly to PTE in select patient populations.…”
Section: Future Directionsmentioning
confidence: 97%
“…Such an approach would involve employing combinations of pulmonary endarterectomy, BPA and medical therapy to target proximal, distal and microvascular disease in the same patient. While initial reports have demonstrated that this approach has potential [82][83][84], further prospective studies are warranted to determine the role that hybrid strategies can play in the future management of CTEPH.…”
Section: Future Perspectivesmentioning
confidence: 99%